Experimental Study of Steel and Polypropylene Fiber Reinforced Concrete (OODBODHAN, 2024)
Fiber-reinforced concrete (FRC) is a composite material incorporating cement, sand, coarse aggregates, and fibers. FRC use both natural and artificial fibers as reinforcement to improve the mechanical properties. This study investigated the effects of two types of artificial fiberssteel and polypropylene—on concrete properties. Steel fiber reinforced concrete (SFRC) with 2% fiber by volume and polypropylene fiber reinforced concrete (PFRC) with 1.5% fiber by volume were prepared. A total of eighteen specimens were made using M20 grade concrete: six cubes, six cylinders, and six beams for each type of fiber. Mechanical properties were tested under compression, including compressive strength, split-tensile strength, and flexural strength. Results showed that PFRC with 1.5% polypropylene fiber exhibited a 23.4% increase in compressive strength, a 32.2% increase in split-tensile strength, and a 20% increase in flexural strength compared to conventional concrete. SFRC with 2% steel fiber demonstrated a 27.2% increase in compressive strength, a 42.7% increase in split-tensile strength, and a 35.8% increase in flexural strength compared to conventional concrete.